The reorganization of the Journal of Sociomuseology New Series nº1-2013 vol. 45 (Cadernos de Sociomuseologia, 2014)
We now begin the publication of the New Series of Cadernos de Sociomuseologia as a result of a reorganization process, still in progress, which aims to improve the performance of the Journal by adopting fully the international guidelines for scientific publications, in particular as regards its indexing and international accreditation. This measure is part of the wider reorganization of the former Center for Research in Sociomuseology (CISMUS), created in 1993, which culminated with their integration into a broader Research Unit called Centre for Interdisciplinary Studies in Education and Development (CEIeD) where it occupies a prominent place in the framework of the Research Line 3 - Culture and Memory Territory.Under this reorganization, the need for which was felt long, several initiatives have been taken towards the establishment of a policy of dissemination better structured, with the aim of strengthening international dimension, and simultaneously provide the Department of Museology with adequate means to support the scientific research conducted by our faculty and researchers in which naturally are included students of Masters and PhD in Museology. Concerning the publication of selected dissertations and theses, which until now were made in the Collection Postgraduate studies, in future shall be published independently. On the other hand, the volumes of "Sociomuseology Collection", in English, will be included in the Cadernos de Sociomuseologia. We believe that this measures will contribute to greater recognition of the place of the Cadernos de Sociomuseologia have occupied in the development of Museology as specific area of expertise, particularly in Portugal and Brazil, and thus open up further cooperation with other national and international institutions.The Editorial Board